Evaluation of Medicinal Constituent (Gingerol) in Iraq Cultivated Ginger: Muhannad A.A. AL-Bayaty , Falah J. Ibrahim & Mohammad W. Hayani - AL-Bayaty, Muhannad A.A. (The Iraqi Journal of Veterinary Medicine, 2006)
The evaluation of gingerol as medical entities in Iraq and Jamaica cultivatedginger was done in this experiment. Two different types of cultivated ginger(Iraq and Jamaica) of the same species (Zingiber officinal) were extracted toachieve the subject of this study. Extraction was performed by two differentstages: the first stage preparative and extraction. Harvested ginger was preparedfor extraction by wash, denotation, drying, grinding, and extracting by acetoneunder heating. The second stage is separation by two steps via TLC and HPLC.The quality and quantity of oleoresin and gingerol in each step of separationwere checked by spots diameter and RF value of spot migration in TLC gingercompounds and quality of whole extract and number of peak in HPLC as well asquantity of gingerol after HPLC separation was done for both Iraqi and Jamaicaginger. The results of comparison between cultivated ginger of Iraq and Jamaicashowed significant decrease (P<0.05) in quantity of extracts and spot diameterof oleoresin where as no significant change (P<0.05) in gingerol quantities byHPLC separation was found in Iraqi species. These results showed no effect ofdifferent cultivation conditions of both peak Jamaica and Iraq species onmedical entities of ginger content of gingerol.